Analisis Perilaku Konsumen Dan Keamanan Kartu Kredit Perbankan - Decky Hendarsyah (Jurnal Perbankan Syariah)
This paper discusses consumer behavior and banking credit card security. Credit cards are present as one of the non-cash payment methods that simplify business and financial matters so that many consumers use them. After review and discussion, it was found that consumer behavior in using credit cards is more dominated by personal factors. With the drive for needs and lifestyle, many consumers are interested in using a credit card. The bank as a credit card issuer also provides sophisticated and multi-layered security features. Even so, it still has a gap for the presence of fraud crime in various ways and forms. In order for credit cards to be safe from crime and fraud, consumer behavior must be changed by maintaining confidentiality, caution and vigilance in conducting transactions.